Posterior ankle arthroscopic treatment of a talar chondroblastoma with allograft and a platelet-rich plasma-fibrin glue: A case report and literature review - Chen, Cheng; Li, ZhenDong; Xue, JianFeng; Shi, ZhongMin (Frontiers in Surgery, 2023)
Talar chondroblastoma is an uncommon but easily missed diagnosis of foot pain. Arthroscopic treatment for talar chondroblastoma is a safe, powerful, and promising technique with definitive advantages of visualization and minimal invasion. We report a case of a talar chondroblastoma treated by posterior ankle arthroscopic curettage, allograft bone graft, and platelet rich plasma-fibrin glue (PRP-FG) application.